2019
DOI: 10.1007/s40544-019-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of airborne wear debris produced by brake pads pressed against HVOF-coated discs

Abstract: A significant fraction of the non-exhaust particulate matter emissions from vehicular traffic comprises fine particles from the wear debris of brake pads and discs. Recent studies have shown that these emissions can be consistently reduced by using wear resistant disc coatings. This study thoroughly analyses the debris produced by a low-met brake pad, which is dyno-bench tested against both cast iron and WC-CoCr-coated brake discs. To achieve this, particles in the size range of 2.5 m to 30 nm were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…For improving the tribological properties of cast-iron discs, some researchers have proposed cryogenic treatments [69,70], conventional heat treatment processes, viz. quenching, tempering, and austempering [48,58,71], and coatings [18,72]. The cryogenic treatment, involving liquid nitrogen, affects not just the surface but the entire cross-section of the disc and improves its wear resistance.…”
Section: Cast Iron Discsmentioning
confidence: 99%
See 2 more Smart Citations
“…For improving the tribological properties of cast-iron discs, some researchers have proposed cryogenic treatments [69,70], conventional heat treatment processes, viz. quenching, tempering, and austempering [48,58,71], and coatings [18,72]. The cryogenic treatment, involving liquid nitrogen, affects not just the surface but the entire cross-section of the disc and improves its wear resistance.…”
Section: Cast Iron Discsmentioning
confidence: 99%
“…Moreover, the coated discs perform better than uncoated ones in terms of particle emissions, as demonstrated in a study, using pin-on-disc (PoD, see Section 3.1.2) testing [72]. Menapace et al [18] conducted a comparative investigation on the emissions from uncoated and WC-CoCr-coated cast iron discs against the same LM pads, using a dyno-bench test rig. From the characterization of the collected particles, in the 2.5 µm to 30 nm range, a consistent reduction in the emission, along with the concentration of iron oxide, was evidenced.…”
Section: Cast Iron Discsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were quite promising, showing that this kind of coating can effectively contribute to the reduction of particulate matter emissions. Menapace et al [39] extended the study, investigating the chemical and phase composition of the airborne fraction of wear debris collected during dyno-bench tests with WC-CoCr coated discs. One of the main results of the investigation was the detection of some critical components transferred from the coating to the airborne fraction of wear debris, including WC and Co.…”
Section: Hvof Cermet Coatings For Brake Discsmentioning
confidence: 99%
“…The study of Wahlström et al [18] demonstrated that significant potential of HVOF cermet coatings in reducing the emission of airborne particles associated with the material wear of braking systems. Similarly, Menapace et al [19] extended the study to investigate the chemical and phase compositions of the airborne fractions of wear debris collected during dyno-bench tests using WC-CoCr-coated discs. One of the main results of the investigation was the detection of critical elements transferred from the coating to the airborne fraction of the wear debris, i.e., cobalt; this has raised additional concern.…”
Section: Introductionmentioning
confidence: 99%